PREDICTORS OF NO-REFLOW PHENOMENON AFTER PCI IN PAKISTANI PATIENTS - KHAN, WA; VISHNO, HR; SHAIKH, SA; MEMON, A; KHAN, R (Biological and Clinical Sciences Research Journal, 2024)
The no-reflow phenomenon is a perplexing complication of PCI. It is marked by poor coronary microvascular perfusion despite successful revascularization. This condition can lead to adverse outcomes such as myocardial infarction and heart failure. Various treatments exist, including pharmacological agents and mechanical interventions, but no flow remains a significant clinical challenge. Objective: This study aims to identify predictors of the no-reflow phenomenon in Pakistani patients undergoing PCI. Methods: Conducted at the National Institute of Cardiovascular Diseases (NICVD) in Karachi from January 2020 to December 2021, this observational study included 256 patients undergoing primary PCI for acute myocardial infarction. Baseline characteristics such as age, sex, BMI, diabetes status, hypertension, smoking status, and left ventricular ejection fraction (LVEF) were recorded. The primary outcome was the incidence of no-reflow, with secondary outcomes including in-hospital mortality and heart failure. Data analysis was performed using SPSS software, with logistic regression pinpointing independent predictors of no-reflow. Results: The patients had a mean age of 58.4 ± 12.3 years, and the median was 59 years. Most patients were male (78.1%). Significant predictors of no-reflow included diabetes mellitus (OR: 2.1, 95% CI: 1.2-3.7, p=0.01), hypertension (OR: 1.8, 95% CI: 1.0-3.2, p=0.04), and reduced LVEF (OR: 1.5 per 5% decrease, 95% CI: 1.2-2.1, p<0.001). Patients experiencing no-reflow had higher in-hospital mortality (11.1% vs. 4.0%, p<0.05) and heart failure rates (24.1% vs. 10.4%, p<0.01) compared to those with normal flow. Conclusion: Diabetes mellitus, hypertension, and reduced LVEF are significant predictors of the no-reflow phenomenon in Pakistani patients undergoing PCI. Identifying high-risk patients allows for targeted preventative strategies to improve clinical outcomes.